LTE-U：the propellant for development of future mobile communication system - Sicong ZHAO; Lei HUANG; Bin SHEN; Xiaoge HUANG (Dianxin kexue)
Recently，a new technology called LTE-U proposed by 3GPP is under study. It aims to relieve the pressure in licensed spectrum. Firstly，an overview of LTE-U was presented，and then the working frequency spectrum and design principles were analyzed. The possible deployment scenarios and operation modes of LTE-U were also summarized. The difficulties in deploying LTE-U and existing solutions were discussed particularly. Finally，several possible future research directions of LTE-U were presented.